2006
DOI: 10.1290/0601004.1
|View full text |Cite
|
Sign up to set email alerts
|

Myoepithelial Molecular Markers in Human Breast Carcinoma Pmc42-La Cells Are Induced by Extracellular Matrix and Stromal Cells

Abstract: The microenvironment plays a key role in the cellular differentiation of the two main cell lineages of the human breast, luminal epithelial, and myoepithelial. It is not clear, however, how the components of the microenvironment control the development of these cell lineages. To investigate how lineage development is regulated by 3-D culture and microenvironment components, we used the PMC42-LA human breast carcinoma cell line, which possesses stem cell characteristics. When cultured on a two-dimensional glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Primary human normal mammary fibroblasts (NMF) and breast cancer-associated fibroblasts (CAF) were previously described [15,16] Quantitative Real-time PCR All RNA preparations were extracted and purified via column chromatography (RNeasy kit, Qiagen, Doncaster, Victoria, Australia) as recommended by the manufacturer. The concentration and purity of RNAs was determined using spectrophotometry (Nanodrop ND-1000 spectrophotometer, Thermo Fisher Scientific, Scoresby, Victoria, Australia).…”
Section: Cell Lines and Mammary Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary human normal mammary fibroblasts (NMF) and breast cancer-associated fibroblasts (CAF) were previously described [15,16] Quantitative Real-time PCR All RNA preparations were extracted and purified via column chromatography (RNeasy kit, Qiagen, Doncaster, Victoria, Australia) as recommended by the manufacturer. The concentration and purity of RNAs was determined using spectrophotometry (Nanodrop ND-1000 spectrophotometer, Thermo Fisher Scientific, Scoresby, Victoria, Australia).…”
Section: Cell Lines and Mammary Fibroblastsmentioning
confidence: 99%
“…We found that CAF-conditioned medium induced myoepithelial molecular markers and increased the migratory ability of the epithelial breast cancer cell line PMC42-LA in a 3D organoid model [15,16]. We used the chemiarray system to examine specific soluble factor(s) in CAF-conditioned media that may be induce this EMT.…”
Section: Cancer-associated Fibroblasts As a Potential Source Of Il-6 mentioning
confidence: 99%
“…We have previously shown the epithelial-like human breast carcinoma PMC42-LA subline undergoes an EMT-like change in response to EGF treatment [27], and in response to factors secreted by human breast carcinoma-derived stromal cells [28,36,37]. It also undergoes EMT at the monolayer wound edge in "scratch" assays which is synergistic with EGF-induced EMT (M. Leigh Ackland, unpublished observation).…”
Section: Introductionmentioning
confidence: 95%